COMPARISON OF ARRANGEMENTS FOR THE CRIME OF CATTLE THEFT ACCORDING TO THE CRIMINAL CODE AND THE DRAFT CRIMINAL CODE - MUH. HASRUL; HAERANAH; SYARIF SADDAM RIVANIE PARAWANSA; AUDYNA MAYASARI MUIN (Awang Long Law Review, 2021)
The crime of cattle theft is regulated in Article 363 paragraph (1) number 1 of the Criminal Code, where the qualification of this crime is categorized as a crime against property. The cattle theft is included in the theft by weight or qualified theft. Based on the formulation of the elements regulated in Article 363, cattle theft is qualified as a formal offense. Meanwhile in the Draft Criminal Code, the cattle theft is still regulated in Article 483 paragraph (1) point c. However, in contrast to the formulation in the Criminal Code, the cattle theft has expanded not only regulated cattle but also goods that are a source of livelihood or a person's main source of livelihood.